Methylamine-free perovskite solar cell and preparation method thereof
By adding formidine acetate (FAAc) as an additive to replace MACl, the stability of perovskite solar cells in the air is solved, and efficient and stable perovskite film preparation is achieved, which improves the long-term performance of the battery.
Patent Information
- Application Number
- CN202411713606.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
Preparing efficient and stable perovskite solar cells in the air faces stability problems, especially because the addition of methyl ammonium chloride (MACl) causes the material to easily decompose in the air, affecting the long-term performance of the battery.
By adding 1% to 10% formicamidine acetate (FAAc) as an additive to the perovskite precursor solution, instead of MACl, perovskite solar cells were prepared.
It effectively reduces the reaction of perovskites with moisture in the air, significantly improves the stability and performance of perovskite films, and improves the long-term stability of the battery and photovoltaic conversion efficiency.
Smart Images

Figure CN119546040A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to a methylamine-free perovskite solar cell and a preparation method thereof. Background Art
[0002] Perovskite solar cells have attracted widespread attention in the photovoltaic field due to their high efficiency, low cost and simplicity of preparation process, and are regarded as one of the most promising solar cell technologies. In just a few years, the photoelectric conversion efficiency of perovskite solar cells has reached 26.8%. In order to promote the industrialization of perovskite solar cells, it is necessary to complete their preparation process in the air. However, a fact that cannot be ignored is that most of the reported perovskite solar films are prepared in an oxygen-free inert atmosphere, and there are relatively few methods for preparing efficient and stable perovskite solar films in an air atmosphere. The core challenge of preparing perovskite solar cells in air is to ensure the long-term stability of the cells. Compared with silicon-based solar cells with a design life of up to 25 years, the stability problem of perovskite solar cells has become a key bottleneck restricting their commercialization.
[0003] The light-absorbing layer of perovskite solar cells has a unique ABX3 structure. In this structure, the A position is usually occupied by a monovalent cation, such as methylamine ion CH3NH3 + (MA + ), formamidinium ion HC(NH2)2 + (FA + ) and cesium ions (Cs + ) and so on. Among the perovskite structures composed of many A-site cations, FAPbI3 exhibits better thermal stability and a more suitable optical band gap than MAPbI3. These characteristics make FAPbI3 a more ideal material choice. However, in the process of preparing high-efficiency FAPbI3 films in air, methylammonium chloride (MACl) is often required to improve the crystallization quality and promote the phase transition of FAPbI3 from δ phase to α phase (Leyu B.et al.Am.Chem.Soc.2023,145,5920-5929). But the addition of MACl also brings side effects, for example, MA + They will occupy the perovskite lattice. During the subsequent annealing process, these ions tend to escape, thus affecting the stability of the perovskite octahedral structure, inducing the formation of defects, and affecting the performance of the battery. + This makes the perovskite easily react with water in the air, causing the perovskite to further decompose and form lead iodide. In addition, MACl absorbs water from the atmosphere and dissolves to form MA + , M.A. +The escape and water absorption decomposition of MA not only seriously damage the structural integrity of the material, but also have a profound impact on the overall performance and long-term stability of the device. + Perovskite has become a research focus. However, due to the role of MACl in promoting phase transition, removing MACl may lead to an increase in the δ non-photoelectric phase in the perovskite film, thereby affecting the device performance. Therefore, how to replace MACl while maintaining excellent performance has become an important topic in the current research of perovskite solar cells.
[0004] Based on this, the present invention designs an innovative method to replace the additive MACl in the precursor solution and successfully prepares efficient and stable perovskite films in air. Summary of the invention
[0005] One of the purposes of the present invention is to provide a methylamine-free perovskite solar cell, comprising a perovskite light-absorbing layer, wherein the perovskite light-absorbing layer is prepared by adding an additive having a molar ratio of 1% to 10% to a perovskite precursor solution;
[0006] The perovskite material in the perovskite light-absorbing layer is an ABX3 type compound, wherein A is a formamidinium ion (FA + ) or formamidinium ion (FA + ) and cesium ions (Cs + ) mixture; the B position is lead ion (Pb 2+ ) or tin ions (Sn 2+ ); X is selected from iodide ion (I - ), bromide ion (Br - ), chloride ion (Cl - );
[0007] The structural formula of the additive is R-COO - M + , wherein R is hydrogen, alkyl or aryl, M + represents metal cations or organic cations, such as amine or amidine compound ions.
[0008] Furthermore, in the formamidinium ion (FA + ) and cesium ions (Cs + ) in a mixture of formamidinium ion (FA + ) content is 20%-100%.
[0009] Furthermore, the additive is selected from formamidine acetate (FAAc), cesium acetate (CsAc), lead acetate (PbAc), and cesium formate (CsFa).
[0010] In one embodiment of the present invention, the perovskite Cs 0.05 FA 0.95Formamidine acetate (FAAc) is added to PbI3 as an additive, and the Cs 0.05 FA 0.95 The molar ratio of PbI3 and FAAc is 1:0.01-0.1.
[0011] Furthermore, the methylamine-free perovskite solar cell is a single-junction solar cell or a stacked solar cell.
[0012] The second object of the present invention is to provide a method for preparing the above-mentioned perovskite solar cell, comprising the following steps:
[0013] A perovskite precursor solution is prepared, an additive is added thereto, and then the mixed solution is coated, and a perovskite light-absorbing layer is obtained after annealing.
[0014] A third object of the present invention is to provide a photovoltaic module, comprising the above-mentioned methylamine-free perovskite solar cell.
[0015] Compared with the prior art, it has the following beneficial effects:
[0016] First, since the precursor does not contain MA + , effectively reducing the reaction between perovskite and moisture in the air, significantly reducing its decomposition in the air, and improving the quality of perovskite films prepared in the air. + , Cs + , Pb + It has a higher volatile temperature and can stably exist in the lattice at a higher temperature, while MA with a lower volatile temperature + It is easy to escape from the lattice at high temperature. - M + -COO in additives - With Pb 2+ The combination forms an intermediate that effectively hinders the rapid reaction of the precursor solute during annealing and avoids the disordered crystal growth. - The volatilization temperature is low. During the annealing process, -COO - Escape, I - Migrate to the crystal lattice to replace -COO - position, thus obtaining a large grain size and uniform and dense perovskite film. - It reduces the number of pores and grain boundaries, lowers defect density, and thus improves charge transport and reduces charge recombination. -COO - As a pseudohalogen, it can remain in the crystal lattice in small amounts, because its ionic radius (0.162nm) is smaller than that of I - The ionic radius (0.220nm) is small and can replace I in the lattice- , reducing lattice stress and making the FAPbI3 ideal factor close to 1, thereby improving film stability. - During the annealing process, the transition of FAPbI3 from the δ non-photoelectric phase to the α photoelectric phase was promoted, and the crystal growth of the film was regulated. - M + Additives can effectively replace MACl to improve film crystallinity and promote phase transition. Using FAAc as the preferred additive can greatly improve the stability of the device while maintaining high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the SEM of the perovskite light absorbing layer with MACl added in Comparative Example 1 and the perovskite light absorbing layer with FAAc added in Example 1.
[0018] Figure 2 The photoluminescence spectra (PL) of the perovskite light absorbing layer with MACl added in Comparative Example 1 and the perovskite light absorbing layer with FAAc added in Example 1.
[0019] Figure 3 1 is a JV curve diagram of the perovskite solar cell of Comparative Example 1 and Example 1.
[0020] Figure 4 This is a steady-state test of the perovskite solar cells of Comparative Example 1 and Example 1 under N2 atmosphere.
[0021] Figure 5 1 and 1 are efficiency decay curves of the perovskite solar cells of comparative example 1 and example 1 after continuous heating at 85° C. in a N2 atmosphere. DETAILED DESCRIPTION
[0022] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.
[0023] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0024] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0025] Comparative Example 1
[0026] This embodiment is a sample before improvement, that is, MACl is added to the perovskite precursor as an additive.
[0027] (1) The ITO conductive glass substrate was cleaned with deionized water and then placed in isopropanol for 30 minutes for ultrasonic treatment. The residual isopropanol was blown off with nitrogen and then placed in a UV ozone cleaning machine for 15 minutes.
[0028] (2) Add 20 mg / mL NiO X The aqueous solution was spin-coated on the treated substrate at a speed of 4000 r / min for 10 s, and then transferred to 100 °C for annealing for 10 min.
[0029] (3) Spin-coat a mixed SAM molecule of Me-4PACz:MeO-2PACz=1:1 dissolved in isopropanol at 0.3mmol / mL on the surface of nickel oxide, with an immersion time of 30s, a spin-coating speed of 3000r / min, and a spin-coating time of 20s. Then transfer to 100°C for heat treatment for 5-10min, then wash with 200uL isopropanol and transfer to 100°C for heat treatment for 5-10min again.
[0030] (4) CsI, FAI, and PbI2 were weighed in a nitrogen glove box according to the molar ratio. The perovskite component was Cs 0.05 FA 0.95 PbI3 was dissolved in a mixed solution of 2-ME and DMSO, with a volume ratio of 2-ME:DMSO = 4:1, and a precursor concentration of about 1.2 mol / L. Then, 10% MACl was added thereto. In a drying room with a humidity of 20%, the perovskite precursor was scraped at a speed of 20 mm / s using a one-step scraping method. The distance from the blade to the substrate was 200 mm. After that, it was placed in a vacuum chamber and evacuated for 60 seconds, with a vacuum degree of 1*10 -3 , and annealed on a hot plate at 150°C for 20 min to obtain a crystallized perovskite light-absorbing layer.
[0031] (5) The substrate with the perovskite light absorbing layer deposited thereon was transferred to a thermal evaporation device, and 30 nm of C 60 , 10nm BCP as the electron transport layer and 200nm Cu as the back electrode to obtain a single-junction perovskite solar cell device.
[0032] Example 1
[0033] This example is an improved sample, that is, FAAc is added to the perovskite precursor as an additive, and a conventional bandgap inverted structure perovskite solar cell is prepared according to the above precursor formula and perovskite film preparation method.
[0034] The solar cell of this embodiment is prepared by referring to the preparation method of Comparative Example 1, except that step (4) is: weigh CsI, FAI, and PbI2 in a nitrogen glove box according to the molar ratio, and the perovskite component is Cs 0.05 FA 0.95 PbI3 was dissolved in a mixed solution of 2-ME and DMSO, with a volume ratio of 2-ME:DMSO = 4:1, and a precursor concentration of about 1.2 mol / L. Then FAAc was added at a molar ratio of 5%. In a drying room with a humidity of 20%, the perovskite precursor was scraped at a speed of 20 mm / s using a one-step scraping method. The distance from the blade to the substrate was 200 mm. Then, it was placed in a vacuum chamber and evacuated for 60 seconds, with a vacuum degree of 1*10 -3 , and annealed on a hot plate at 150°C for 20 min to obtain a crystallized perovskite light-absorbing layer.
[0035] Figure 1 The SEM images of the perovskite light absorbing layer prepared in step 4 of comparative example 1 and the perovskite light absorbing layer prepared in step 4 of example 1 show that, compared with MACl, the film prepared with FAAc as an additive has fewer pores and larger grain size.
[0036] Figure 2 The photoluminescence spectra (PL) of the perovskite light absorbing layer prepared in step 4 of comparative example 1 and the perovskite light absorbing layer prepared in step 4 of example 1 show that the carrier lifetime of the perovskite film with MACl added is 102 ns, while the carrier lifetime of the perovskite film with FAAc added is 157 ns, which indicates that the defects are reduced and the carrier lifetime is increased after adding FAAc.
[0037] like Figure 3 As shown, the device efficiency of solar cells is significantly improved after adding FAAc compared with MACl.
[0038] like Figure 4 As shown, the device stability of solar cells is greatly enhanced after adding FAAc compared with MACl.
[0039] like Figure 5 As shown, the stability of the solar cell at 85 °C is significantly improved after adding FAAc compared with MACl.
[0040] Example 2
[0041] This example is an improved sample, that is, CsAc is added to the perovskite precursor as an additive, and a conventional bandgap inverted structure perovskite solar cell is prepared according to the above precursor formula and perovskite film preparation method.
[0042] The solar cell of this embodiment is prepared by referring to the preparation method of Comparative Example 1, except that step (4) is: weigh CsI, FAI, and PbI2 in a nitrogen glove box according to the molar ratio, and the perovskite component is Cs 0.05 FA 0.95 PbI3 was dissolved in a mixed solution of 2-ME and DMSO, with a volume ratio of 2-ME:DMSO = 4:1, and a precursor concentration of about 1.2 mol / L. Then, 5% CsAc was added thereto. In a drying room with a humidity of 20%, the perovskite precursor was scraped at a speed of 20 mm / s using a one-step scraping method. The distance from the blade to the substrate was 200 mm. Then, the substrate was placed in a vacuum chamber and evacuated for 60 seconds, with a vacuum degree of 1*10 -3 , and annealed on a hot plate at 150°C for 20 min to obtain a crystallized perovskite light-absorbing layer.
[0043] Example 3
[0044] This example is an improved sample, that is, PbAc is added to the perovskite precursor as an additive, and a conventional bandgap inverted structure perovskite solar cell is prepared according to the above precursor formula and perovskite film preparation method.
[0045] The solar cell of this embodiment is prepared by referring to the preparation method of Comparative Example 1, except that step (4) is: weigh CsI, FAI, and PbI2 in a nitrogen glove box according to the molar ratio, and the perovskite component is Cs 0.05 FA 0.95 PbI3 was dissolved in a mixed solution of 2-ME and DMSO, with a volume ratio of 2-ME:DMSO = 4:1, and a precursor concentration of about 1.2 mol / L. Then, 5% PbAc was added thereto. In a drying room with a humidity of 20%, the perovskite precursor was scraped at a speed of 20 mm / s using a one-step scraping method. The distance from the blade to the substrate was 200 mm. Then, the substrate was placed in a vacuum chamber and evacuated for 60 seconds, with a vacuum degree of 1*10 -3 , and annealed on a hot plate at 150°C for 20 min to obtain a crystallized perovskite light-absorbing layer.
[0046] Example 4
[0047] This example is an improved sample, that is, CsFa is added to the perovskite precursor as an additive, and a conventional bandgap inverted structure perovskite solar cell is prepared according to the above precursor formula and perovskite film preparation method.
[0048] The solar cell of this embodiment is prepared by referring to the preparation method of Comparative Example 1, except that step (4) is: weigh CsI, FAI, and PbI2 in a nitrogen glove box according to the molar ratio, and the perovskite component is Cs 0.05FA 0.95 PbI3 was dissolved in a mixed solution of 2-ME and DMSO, with a volume ratio of 2-ME:DMSO = 4:1, and a precursor concentration of about 1.2 mol / L. Then, 5% CsFa was added thereto. In a drying room with a humidity of 20%, the perovskite precursor was scraped at a speed of 20 mm / s using a one-step scraping method. The distance from the blade to the substrate was 200 mm. Then, the substrate was placed in a vacuum chamber and evacuated for 60 seconds with a vacuum degree of 1*10 -3 , and annealed on a hot plate at 150°C for 20 min to obtain a crystallized perovskite light-absorbing layer.
[0049] The perovskite solar cells prepared in the above examples were tested, and the results are shown in the following table:
[0050] Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) PCE(%) Comparative Example 1 1.07 23.44 80.08 20.01 Example 1 1.15 24.55 79.47 22.35 Example 2 1.13 24.21 80.06 21.93 Example 3 1.10 24.13 81.59 21.61 Example 4 1.12 23.50 80.66 21.21
[0051] It can be seen from the table that the open circuit voltage and photovoltaic conversion efficiency of the battery in Examples 1-4 are better than those in Comparative Example 1, and when FAAc is selected as the additive, the efficiency can reach 22.35%.
Claims
1. A methylamine-free perovskite solar cell, characterized in that: It includes a perovskite light absorbing layer, which is prepared by adding an additive with a molar ratio of 1% to 10% to a perovskite precursor solution; The perovskite material in the perovskite light-absorbing layer is an ABX3 type compound, wherein A is a formamidine ion or a mixture of a formamidine ion and a cesium ion; B is a lead ion or a tin ion; and X is selected from an iodine ion, a bromide ion, and a chloride ion; The structural formula of the additive is R-COO - M + , wherein R is hydrogen, alkyl or aryl, M + It is a metal cation or an organic cation.
2. The perovskite solar cell according to claim 1, characterized in that The content of formamidinium ions in the mixture of formamidinium ions and cesium ions is above 20%.
3. The perovskite solar cell according to claim 1, characterized in that The additive is selected from formamidine acetate, cesium acetate, lead acetate, and cesium formate.
4. The perovskite solar cell according to claim 1, characterized in that: The perovskite solar cell is a single-junction solar cell or a stacked solar cell.
5. A method for preparing a methylamine-free perovskite solar cell according to any one of claims 1 to 4, characterized in that: The following steps are involved: A perovskite precursor solution is prepared, an additive is added thereto, and then the mixed solution is coated, and a perovskite light-absorbing layer is obtained after annealing.
6. A photovoltaic module, characterized in that: A methylamine-free perovskite solar cell comprising the method of any one of claims 1 to 4.
Citation Information
Patent Citations
Phase stabilizer and method for preparing perovskite solar cell by using same
CN112349845A
Method for preparing FAPbI3 perovskite thin film and efficient perovskite solar cell by using FAPbI3 perovskite thin film
CN114678472A
Perovskite thin film, preparation method thereof and solar cell
CN116419642A
Perovskite solar cell regulated and controlled by guanidyl amino acid additive and preparation method of perovskite solar cell
CN117396006A
Cesium-formamidine-based lead-iodine alloy perovskite active layer and preparation method and application thereof
CN117794334A